The Topology of Time Series: Improving Recession Forecasting from Yield Spreads - Simon Rudkin (EconPapers, 2019)
Recession forecasting ranges from the simplistic inference from witnessing an inverted yield curve to sophisticated models drawing data from across the macroeconomic and financial spectra. Each has advantages, in simplicity and informativeness respectively, but each suffers for these. Demonstrating how the properties of yield spread time series can foretell of impending recessions we introduce data topology to economics. Through an exploration of the topology of time series we highlight an untapped source of information with the potential to significantly improve understanding of the economy. Advantageously we do so without risking the overfitting of introducing other variables.